2020
DOI: 10.1155/2020/3259393
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lymph Node Status and Expression Levels of Androgen Receptor, miR-185, miR-205, and miR-21 in Breast Cancer Subtypes

Abstract: Breast cancer is the most commonly diagnosed cancer among women. Difficulties in treating breast cancer are associated with the occurrence of metastases at early stages of disease, leading to its further progression. Recent studies have shown that changes in androgen receptor (AR) and microRNAs’ expressions are associated with mammary gland carcinogenesis, in particular, with the formation of metastases. Thus, to identify novel metastatic markers, we evaluated the expression levels of AR; miR-185 and miR-205, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…We have also previously shown miR-21 levels in HER2-expressing BC may be associated with the presence of LNM [11]. Here, when using a larger sample, we observed only a tendency to an increase in the miR-21 level in the tissues of patients with LNM compared to cases without, in HER2-expressing BC with Ki-67 ≥ 14%.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We have also previously shown miR-21 levels in HER2-expressing BC may be associated with the presence of LNM [11]. Here, when using a larger sample, we observed only a tendency to an increase in the miR-21 level in the tissues of patients with LNM compared to cases without, in HER2-expressing BC with Ki-67 ≥ 14%.…”
Section: Discussionsupporting
confidence: 52%
“…According to previous studies, AR expression correlates with ER status [40]. We have also previously shown that in luminal B HER2 0 BC, AR level is higher for tumors with ER IHC scores of 6-8 compared to tumors with ER IHC scores of 0-5 [11]. Considering that miR-200b is an AR-regulated miRNA, the observed decrease in its levels in tumors with lower ER levels may be due to lower AR expression.…”
Section: Discussionmentioning
confidence: 57%
“…We also found that under the action of p , p ′‐DDT, the expression of ER, PR, and AR decreases after 48 h. In general, low expression of these receptors in luminal breast cancer subtypes correlates with a more aggressive course of the disease and a worse prognosis. [ 46–49 ] After incubation with 1 μM endosulfan, PR expression decreased after 48 h and AR expression decreased after 24 h. In contrast, under the influence of o , p ′‐DDT, the level of AR mRNA slightly increased. Both testosterone and estradiol treatment resulted in ER underexpression but PR overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published protocols were used for miRNA and total RNA isolation, miRNA and RNA reverse transcription, and real-time PCR to determine miRNA and mRNA levels [ 15 ]. Total RNA was isolated using the TRIzol™ reagent (Invitrogen, USA).…”
Section: Methodsmentioning
confidence: 99%